Resection of Large Urological Tumors With or Without Inferior Vena Cava Extension in Jehova's Witnesses - Ciancio, Gaetano; Gonzalez, Javier (Frontiers in Surgery, 2020)
Background: Renal and adrenal tumors with/without tumor thrombus in the inferior vena cava (IVC) pose a challenge to the surgeon due to the potential for massive hemorrhage and tumor thromboemboli. The situation would be more critical for Jehovah's Witness (JW) patients which refuse blood transfusion. A transplant-based (TB) approach to these tumors in JWs would result a safe surgical method, providing limited blood loss and perioperative complications. We report our experience using a TB surgical approach in JW harboring large adrenal/renal tumors with/without tumor thrombus trying to determine its usefulness in this setting. Patients and Methods: From 2003 to 2011, 7 patients underwent resection of renal/adrenal tumors with/without tumor thrombus in the IVC by means of a TB approach. Thrombus level was renal (n = 2), retrohepatic (n = 1), and suprahepatic (n = 1). The remaining 3 patients did not present thrombus. No pre-operative optimization or cell-saver were used. Estimated blood loss, perioperative complications (Clavien-Dindo and cause), hemoglobin/hematocrit loss, and length of stay were considered main outcomes. Results: The intervention was successfully completed without transfusion in all cases. Operative time and blood loss were 2.5 h (range: 1.83–5.75) and 150 cc (range: 100–750), respectively. No major post-operative complications were registered. However, minor complications were detected in 57% of the patients included. Median hemoglobin loss was 1.13 mg/dL, which translated a median hematocrit loss of 2.3%. Patients were discharged in a median of 7 days (range 5–20). Conclusions: A TB-surgical approach provides enhanced retroperitoneal exposure and optimal vascular control, thus limiting operative blood loss or major complication development, thus resulting useful in JWs.